Territorial networks: Kichwa Lamista nurture relationships and San Martín as «región verde» - Chaparro, Anahí (2021)
This article presents an exercise of symmetric anthropology, following the paths proposed by Latour (1994), comparing two networks - not disconnected from each other – that are linked by different ways of knowing: that of the relationships that constitute the territory of «San Martín, región verde» and that of the Kichwa Lamista nurture relationships, departing from Alto Pucalpillo community. The interest of this article is to approach the bonds that this knowledge activates through its effects, its ways of constituting subjects and producing the territory. On one hand, the intertwining between humans, plants, animals and other beings that share the same environment, as subjects with agency, affections and their own will, forms a network of care, not without tension. On the other hand, the network of actors that participate in the conservation of the “green region” relates to the territory as an objective reality from which it can extract a truth. From a technical-scientific knowledge conceived as neutral, they create maps that define borders in space and between what is legal and what is illegal, at the same time that they question the condition of native communities as subjects of rights. With this, the author does not intend to affirm that there aren’t intersections between de two networks, but rather the need to direct ourselves towards a nutritive coexistence.